Measuring the effects of economic diversity on growth and stability - Wagner, John E.; Deller, Steven C. (1998)
The role of economic diversity in regional stability and growth is examined. Contrary to "conventional wisdom" the empirical literature has been unable to confirm the link between diversity and economic performance. Traditional notions of diversity tend to be defined narrowly, usually emphasizing the distribution of employment across industries. These approaches are inadequate because they do not capture elements of inter-industrial linkages. An alternate approach to conceptualizing diversity, based on a regional input-output model, is described and computed for the 50 states. Empirical results suggest that diversity within the theoretical construct of input-output is associated with higher levels of stability and growth. - Reproduced
Keywords: Economic growth